STRATEGI PENATAAN KAWASAN KOTA LAMA SEMARANG - Hilva Asmania; Herbasuki Nurcahyanto; Mariyam Musawa (Journal of Public Policy and Management Review, 2014)
The government of Semarang initiate old town Revitalization program by the Local Government Regulation No. 8 of 2003 on Spatial Planning and Environment Building (SPEB) Old Town area of Semarang . SPEB is an effort to produce guidelines to develop , organize and relive the Old City . SPEB of Old Town area is expected to support the development and revitalization through urban design . The Urban Planning will be followed by the revitalization which is a long-term program. It Aims to enable the revitalization of the Old Town in accordance with the demands of time and a positive impact for the city of Semarang both in terms of tourism , economic , social , and cultural . However there are some problems in revitalizing the Old Town of Semarang that results in a state of stagnation continues - constantly in the Old  Town of Semarang . The study analyzes the strengths , weaknesses , opportunities , and threats in order to obtain the proper management on strategic arrangement Old Town area of Semarang . The approach used is descriptive qualitative methods of data collection , interviews , and documentation studies . The data that have been collected will be presented and analyzed based on internal and external environment and the conclusions drawn . The conclusion of this study is by  recognizing the strengths , weaknesses , opportunities , and threats based on internal and external environment formulated using SWOT analysis and tested with litmus tests , The Strategic Arrangement of Semarang Old Town obtained as follows: Character building and improvement of Human Resources ( HR ) , Improving the quality of HR through the development of a strong characteristic in the socio-cultural values , Improving object optimal service through the cooperation of various sectors of business and community involved in revitalizing Old Town, Each stakeholder improvement respective roles, Handling and tidal flooding , Providing incentives and ease of investment, Increased cooperation with various business sectors in development , Improved complementary tool is still lacking , as well as increase the participation of local communities and businesses.